Functional reconstitution of the Mycobacterium tuberculosis long-chain acyl-CoA carboxylase from multiple acyl-CoA subunits - Bazet Lyonnet, Bernardo (2017)
Mycobacterium tuberculosis produces a large number of structurally diverse lipids that have been implicated in the pathogenicity, persistence and antibiotic resistance of this organism. Most building blocks involved in the biosynthesis of all these lipids are generated by acyl-CoA carboxylases whose subunit composition and physiological roles have not yet been clearly established. Inconclusive data in the literature refer to the exact protein composition and substrate specificity of the enzyme complex that produces the long-chain α-carboxy-acyl-CoAs, which are substrates involved in the last step of condensation mediated by the polyketide synthase 13 to synthesize mature mycolic acids. Here we have successfully reconstituted the long-chain acyl-CoA carboxylase (LCC) complex from its purified components, the α subunit (AccA3), the ε subunit (AccE5) and the two β subunits (AccD4 and AccD5), and demonstrated that the four subunits are essential for its activity. Furthermore, we also showed by substrate competition experiments and the use of a specific inhibitor that the AccD5 subunit's role in the carboxylation of the long acyl-CoAs, as part of the LCC complex, was structural rather than catalytic. Moreover, AccD5 was also able to carboxylate its natural substrates, acetyl-CoA and propionyl-CoA, in the context of the LCC enzyme complex. Thus, the supercomplex formed by these four subunits has the potential to generate the main substrates, malonyl-CoA, methylmalonyl-CoA and α-carboxy-C24–26-CoA, used as condensing units for the biosynthesis of all the lipids present in this pathogen.